Determinants of Flat Foot Incidence on Early Childhood Posture - Awanis, Almas; Nur Ramadhani, Alinda; Ines Prabandari, Fatchurrohmah (Universitas Muhammadiyah Surakarta, 2025)
Scoliosis is a structural deformity of the spine in the lateral direction with a curvature of ≥10° in the coronal plane. The occurrence of posture disorders towards scoliosis is often only realised in adolescence, namely with an age range of 10-16 years. If you only realise it at this age, then it is too late, because other health problems can arise that affect your future life. Therefore, the existence of this study is expected to be able to make an instrument for the early detection of postural developmental disorders in preschool children against the incidence of scoliosis. From the examination that has been carried out on 94 students, it has been found that 74% of children have normal posture with a degree range of 10 to 40, and 25% of children have been detected with intermediate scoliosis (50 to 70). The next measurement that the researcher made was to measure the degree of arch of the child's foot. Measurements of normal categories of foot, flat foot and cavus foot use Clarke's angle. Clarke's angle is obtained from the meshing angle of the tangent formed by the first line connecting the medial edge of the first metatarsal caput and the heel and the second line connecting the first metatarsal caput with the crest of the medial longitudinal arch. Data was obtained that most children experience flat feet as much as 77%, which is dominated by male children.